A new surgical procedure for type II total anomalous pulmonary venous drainage. (22nd February 2018) - Nakanishi, Keisuke; Kawasaki, Shiori; Amano, Atsushi
Abstract: We report two cases of successful surgical repair of total anomalous pulmonary venous drainage. Our new surgical procedure for type IIa and IIb total anomalous pulmonary venous drainage has more advantages than the conventional rerouting method using an artificial or native pericardial patch.